PEMENUHAN HAK TERHADAP PENYANDANG DISABILITASPENGGUNA JASA ANGKUTAN LAUT PT. ANGKUTAN SUNGAI DANAU DAN PENYEBERANGAN (ASDP) INDONESIA FERRY (STUDI KASUSKAPAL RORO DUMAI - RUPAT) - Rahmat Sandani; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Business actors in providing public services in the field of transportation services must implementand comply with the provisions contained in the Law and other regulations. Then the Dumai-Rupat branchRORO ship in its service has the responsibility for the obligation to guarantee the rights of consumers usingthe Dumai-Rupat branch RORO transportation service. Considering that consumers with disabilities are avulnerable group of people, protection must be given that is more relevant to its specificity, namely LawNumber 8 of 2016 concerning Persons with Disabilities. In the implementation it refers to Law Number 8 of1999 concerning Consumer Protection. But in fact there has been a social inequality towards consumers withdisabilities. Where the Dumai-Rupat branch of the RORO ship does not provide special facilities and facilitiesfor Disabled Persons as stated in Article 2 Paragraph (1) of the Republic of Indonesia Minister ofTransportation Regulation Number PM 98 of 2017 Challenging the Provision of Accessibility in PublicTransportation Services for Service Users with Needs Especially "Organizers of public transportationservices must carry out services for users of special needs services". The problem and purpose to be discussedin this thesis is to find out the form of fulfillment of rights for persons with disabilities as people who use theservices of the Dumai-Rupat RORO vessel.This type of research is sociological, because in this study the author immediately conductedresearch on the location or place under study to provide a complete and clear picture of the problem understudy. This research was conducted at the Riau Province Transportation Agency, PT. ASDP Indonesia FerryDumai-Rupat branch and Dumai-Rupat branch RORO ship. While the population and sample are all partiesrelated to the problems examined in this study, the data sources used, primary data, secondary data andtertiary data, data collection techniques in this study with interviews, questionnaires and literature studies.The results of the study can be concluded that the Department of Transportation of Riau Provinceand PT. ASDP Indonesia Ferry as the manager of the Dumai-Rupat branch of the RORO vessel has not fullyimplemented the consumer rights of persons with disabilities. Special facilities intended for DisabilitySuppressors are not yet available at the port and inside the Dumai-Rupat RORO vessel. With theunavailability of these facilities, consumers with disabilities feel that their rights as consumers are not met bythe Dumai-Rupat branch of the RORO Ship. Suggestions for the Riau Provincial Transportation Agency andPT. ASDP Indonesia Ferry, a branch of Dumai-Rupat in order to be able to better enjoy the rights of personswith disabilities by improving the service and supervision of the Rupai Rupai RORO ship. So that there are norights from consumers with disabilities who are harmed.Keywords: Fulfillment of Rights - Disabled Persons - Service Users - Dumai-Rupat RORO Shi